The Arclight Ophthalmoscope: A Reliable Low-Cost Alternative to the Standard Direct Ophthalmoscope - James Lowe; Charles R. Cleland; Evarista Mgaya; Godfrey Furahini; Clare E. Gilbert; Matthew J. Burton; Heiko Philippin (Journal of Ophthalmology)
Background. The Arclight ophthalmoscope is a low-cost alternative to standard direct ophthalmoscopes. This study compared the Arclight ophthalmoscope with the Heine K180 direct ophthalmoscope to evaluate its reliability in assessing the vertical cup disc ratio (VCDR) and its ease of use (EOU). Methods. Eight medical students used both the Arclight and the Heine ophthalmoscopes to examine the optic disc in 9 subjects. An EOU score was provided after every examination (a higher score indicating that the ophthalmoscope is easier to use). A consultant ophthalmologist provided the reference standard VCDR. Results. 288 examinations were performed. The number of examinations that yielded an estimation of the VCDR was significantly higher for the Arclight ophthalmoscope (125/144, 85%) compared to the Heine ophthalmoscope (88/144, 61%) (p<0.001). The mean difference from the reference standard VCDR was similar for both instruments, with a mean of −0.078 (95% CI: −0.10 to −0.056) for the Arclight and −0.072 (95% CI: −0.097 to −0.046) for Heine (p=0.69). The overall EOU score was significantly higher for the Arclight ophthalmoscope (p<0.001). Conclusion. The Arclight ophthalmoscope performs as well as, and is easier to use than, a standard direct ophthalmoscope, suggesting it is a reliable, low-cost alternative.